Comparing QoS of DSDV and AODV routing protocols in vehicular network - Hassan Poor, A.; Hoodeh, H.; Zarrinnegar, A.; Emami, A.; Noor, R.M. (2012)
With the advance of Vehicular ad-hoc network, routing protocol has become one of the most important issues in transmitting data among Vehicles. The two routing protocol are DSDV and AODV which DSDV is known as a novel approach in proactive system; however, AODV has good performance in reactive system. In this paper, we compare the efficiency between DSDV & AODV in terms of packet-loss, end-to-end delay and throughput based on given scenarios. The comparison has implemented in various speeds for acquiring result with higher performance. The speeds consist of 5, 20 and 40km/s. then we analyze the explicit results according to X-Graph in NS2. Our comparison and evaluation indicate that AODV demonstrate more satisfactory result than DSDV in case of usage in highway.